FAKTOR-FAKTOR PENENTU NILAI PERUSAHAAN: DAMPAK PROFITABILITAS, LEVERAGE, KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN, DAN STRUKTUR MODAL - Marlina, Popy Marlina (Jurnal Manajemen dan Profesional, 2024)
The aim of this research is to test and analyze the influence of profitability, leverage, dividend policy, company size and capital structure on company value (empirical study of companies listed on the Indonesia Stock Exchange period. Sampling in this study used purposive sampling technique. Based on specified criteria, a sample of 21 companies was obtained over 4 years. Data analysis in this study used multiple linear regression analysis with the help of SPSS. The test results show that the variables profitability and capital structure had a positive effect, while the variables leverage, dividend policy and company size had a negative effect on company value.